Between Household and State - Dayal, Subah (California University of California Press, 2024)
Between Household and State departs from dynastic narrations of the Mughal past to highlight the role of elite households and familial networks in peninsular India, the only region of the subcontinent never fully incorporated into the imperial realm. Drawing on rare documentary and literary materials in Persian and Urdu alongside the Dutch East India Company$1 (Bs archives, this book takes readers on a journey from military forts and regional courts in the Deccan to the ports and weaving villages of the Coromandel Coast. It examines how regional elite alliances, feuds, and material exchanges intersected with imperial institutions to create new forms of affinity, belonging, and social exclusion. Subah Dayal brings attention to the importance of ghar$1 (Bor home$1 (Bin the creation of forms of mobility that anchored the Mughal frontier across the variable geography of peninsular India in the seventeenth century.s
Keywords: History; Asian History